PERENCANAAN OPERASIONAL BRITISH PETROLEUM ACTIVE MOBILE FUEL STATION PT WHEZ ENERGI SEJAHTERA - Setiawan, Zatmiko; Indradewa, Rhian; Negoro, Dimas Angga; Hamdi, Edi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
The research objective is to provide a comprehensive understanding of the operational planning of PT Whez Energi Sejahtera (PT WES) in running the British Petroleum Active Mobile Fuel Station (BP Active MFS) service. Starting from the company establishment stage, the regulations and permits required, to the operational design of the company once it is running. This business plan uses a detailed methodological approach, PT WES operational planning is presented using a framework to ensure the British Petroleum Active Mobile Fuel Station (BP Active MFS) can operate effectively and efficiently. The BP Active MFS selection method uses a systematic and objective weighted product method. The findings reveal that well-structured and comprehensive operational planning for the British Petroleum Active Mobile Fuel Station (BP Active MFS) that complies with existing regulations, and can meet customer needs, and can achieve financial viability will be very important for the success of BP Active MFS.